ANALISIS FINANSIAL USAHA TAMBAK UDANG DI KECAMATAN TANJUNG HARAPAN KABUPATEN PASER (Financial Analysis Of Shrimp Farming In Tanjung Harapan Sub-District Paser District) - ANGRAINI, NUR AZIZAH; SUKARTI, KOMSANAH; ERWIANTONO, ERWIANTONO; IRAWAN, IRMAN; IRAWAN, ADITYA; SUSILO, HERU (Universitas Mulawarman (University of Mulawarman), 2025)
The fishing industry is more popular among the community, and one of the reasons for this is the high demand for fishery products, especially shrimp. The Tanjung Harapan sub-district in Paser Regency has considerable potential for pond-based aquaculture, particularly for tiger shrimp (Penaeus monodon). The favorable geographical conditions and promising business opportunities have made this business a source of livelihood for the surrounding community. However, shrimp pond farming is vulnerable to production fluctuations due to climatic factors, pest and disease attacks, and suboptimal management. The purpose of this study is to assess the financial feasibility of pond farming in Tanjung Harapan Subdistrict, Paser Regency. This study uses analysis methods such as Net Present Value (NPV), Net Benefit Cost Ratio (B/C), Internal Rate of Return (IRR), and Payback Period (PP). The results of the study show that the Net Present Value (NPV) for the next five years for the shrimp farming business is IDR 546,335,336, the Net BCR is 8.35 with an IRR of 166%, and the payback period is 7.18 months.